Evaluation of the School Operational Assistance Program Based on Law Number 20 of 2003 concerning National Education (Case study of SMK Rayon III Bekasi City) - Dewi Gunherani (Dinasti Research, 2024)
This research aims to evaluate the implementation of the School Operational Assistance (BOS) program in private Vocational High Schools (SMK) in the Rayon III area of Bekasi City, using a statutory approach and empirical juridical method. The study employs a descriptive method with qualitative analysis based on interviews and secondary data from primary and secondary legal materials. Results show that the implementation of the BOS fund program aligns with Law No. 20/2003 on the National Education System and its implementing regulations, with timely reporting on fund usage and no late fees incurred. Supervision by the Office Branch Office (KCD) of Sub Rayon III Bekasi also complies with relevant provisions. The empirical juridical analysis indicates that the implementation of BOS funds in this area fulfills the elements of legal certainty, justice, and community benefit. This study's implications highlight the importance of enhancing transparency and accountability in BOS fund management, as well as the need for increased supervision to more effectively support educational activities and ensure fair access to quality education.